Direct Fabrication of a Copper RTD over a Ceramic-Coated Stainless-Steel Tube by Combination of Magnetron Sputtering and Sol–Gel Techniques - Aitor Bikarregi; Santiago Dominguez; Marta Brizuela; Alejandra López; Ana Suarez-Vega; Cecilia Agustín-Sáenz; Micael Presa; Gabriel A. López (Sensors, 2023)
Reducing the economic and environmental impact of industrial process may be achieved by the smartisation of different components. In this work, tube smartisation is presented via direct fabrication of a copper (Cu)-based resistive temperature detector (RTD) on their outer surfaces. The testing was carried out between room temperature and 250 °C. For this purpose, copper depositions were studied using mid-frequency (MF) and high-power impulse magnetron sputtering (HiPIMS). Stainless steel tubes with an outside inert ceramic coating were used after giving them a shot blasting treatment. The Cu deposition was performed at around 425 °C to improve adhesion as well as the electrical properties of the sensor. To generate the pattern of the Cu RTD, a photolithography process was carried out. The RTD was then protected from external degradation by a silicon oxide film deposited over it by means of two different techniques: sol–gel dipping technique and reactive magnetron sputtering. For the electrical characterisation of the sensor, an ad hoc test bench was used, based on the internal heating and the external temperature measurement with a thermographic camera. The results confirm the linearity (R2 > 0.999) and repeatability in the electrical properties of the copper RTD (confidence interval < 0.0005).